A Legal Perspective on Social and Business Conflicts of Interest: Ethics Enforcement in GOTO - Muhammad Hermansyah; Endang Fatmawati; Yanti Mulia Roza; Tekat Sukomardojo (UIN Sunan Gunung Djati, 2024)
This study examines the conflict between corporate profit and social responsibility within GOTO’s business model, specifically analyzing how commission and fare deduction policies create legal and ethical dilemmas. Using a qualitative research approach, the study employs a legal analysis framework grounded in corporate governance principles, alongside literature reviews, document analysis, and stakeholder interviews. Findings reveal that prioritizing profitability through these policies results in decreased income and growing dissatisfaction among driver partners, thereby intensifying conflicts of interest. Although GOTO has initiated measures such as the establishment of an Ethics Committee and driver support programs, these steps fall short of fully addressing the legal and ethical gaps. The study concludes that reinforcing specific legal regulations—particularly those ensuring accountability and equitable stakeholder treatment—is crucial for resolving these conflicts. These results underscore the urgent need for adaptive legal policies that better balance corporate profit motives with broader social responsibilities in the digital economy.